A molecular roadmap of definitive erythropoiesis from human induced pluripotent stem cells. (6th January 2017) - Razaq, Muhammad A.; Taylor, Stephen; Roberts, David J.; Carpenter, Lee
Summary: Human induced pluripotent stem cells (hiPSCs) are being considered for use in understanding haematopoietic disorders and as a potential source of in vitro manufactured red cells. Here, we show that hiPSCs are able to recapitulate various stages of developmental erythropoiesis. We show that primitive erythroblasts arise first, express CD31 + with CD235a +, embryonic globins and red cell markers, but fail to express the hallmark red cell transcripts of adult erythropoiesis. When hiPSC‐derived CD45 + CD235a − haematopoietic progenitors are isolated on day 12 and further differentiated on OP9 stroma, they selectively express CD36 + and CD235a +, adult erythroid transcripts for transcription factors (e.g., BCL11A, KLF1 ) and fetal/adult globins ( HBG1/2, HBB ). Importantly, hiPSC‐ and cord‐derived CD36 + CD235a + erythroblasts show a striking homology by transcriptome array profiling (only 306 transcripts with a 2Log fold change >1·5‐ or 2·8‐fold). Phenotypic and transcriptome profiling of CD45 + CD117 + CD235a + pro‐erythroblasts and terminally differentiated erythroblasts is also provided, including evidence of a HbF (fetal) to HbA (adult) haemoglobin switch and enucleation, that mirrors their definitive erythroblast cord‐derived counterparts. These findings provide a molecular roadmap of developmental erythropoiesis from hiPSC sources at several critical stages, but also helps to inform on their use for clinical applications and modelling human haematopoietic disease.